(untitled) (Perspectivas de las Ciencias Económicas y Jurídicas, 2019)
This paper is part of the development of the research project Study of the practice of Legal Psychology in relation to young people in conflict with criminal law. It belongs to the UBACYT 2014-2017 scientific program and is directed by Dr. Varela and the Lic. de la Iglesia. On this occasion we will address the practices exercised with young people in conflict with the law in the period from 1880 to 1919. In 1880, Argentina receives large waves of immigration that settle in the cities, observing an abrupt increase in crime. A considerable part of those who committed these crimes were young. Those young people who came into conflict with the criminal law prior to the Agote Law (1919), were deprived of their liberty for preventive or reeducation reasons. The detention was a legitimized practice for what was known as childhood in material or moral danger or dangerous childhood.